2022
DOI: 10.1002/ctm2.711
|View full text |Cite
|
Sign up to set email alerts
|

LDLR dysfunction induces LDL accumulation and promotes pulmonary fibrosis

Abstract: Treatments for pulmonary fibrosis (PF) are ineffective because its molecular pathogenesis and therapeutic targets are unclear. Here, we show that the expression of low‐density lipoprotein receptor (LDLR) was significantly decreased in alveolar type II (ATII) and fibroblast cells, whereas it was increased in endothelial cells from systemic sclerosis‐related PF (SSc‐PF) patients and idiopathic PF (IPF) patients compared with healthy controls. However, the plasma levels of low‐density lipoprotein (LDL) increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Previous studies have found that reducing the content of lipoprotein in plasma can reduce oxidative stress, release of proin ammatory factors, and maintain the steady state of matrix metalloproteinases (MMP), thus alleviating the occurrence and development of pulmonary interstitial diseases. [10,11]. Ezetimibe, as a lipid-lowering drug, can also prevent the occurrence and development of pulmonary brosis in our study.…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies have found that reducing the content of lipoprotein in plasma can reduce oxidative stress, release of proin ammatory factors, and maintain the steady state of matrix metalloproteinases (MMP), thus alleviating the occurrence and development of pulmonary interstitial diseases. [10,11]. Ezetimibe, as a lipid-lowering drug, can also prevent the occurrence and development of pulmonary brosis in our study.…”
Section: Discussionmentioning
confidence: 50%
“…MCAD and LCAD catalyze the first step of fatty acid oxidation and determine the lipid used for the TCA cycle ( 38 , 39 ). Low-density lipoprotein receptor (LDLR) can bind to LDL and reduce LDL contents in serum ( 40 ). Subtilisin 9 ( PCSK9 ) can negatively regulate the expression of LDLR , resulting in hypercholesterolemia ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary fibrosis is an advanced interstitial lung disease characterized by excessive ECM deposition with poor prognosis [ 15 , 16 ], including silicosis and IPF. Despite the current approved two antifibrotic medicine (nintedanib and pirfenidone) having been shown to reduce lung function decline, there is not enough to postpone fibrosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%